A Third Supernumerary Tooth Occurring in the Same Region: A Case Report - Tatsuya Akitomo; Yuria Asao; Yuko Iwamoto; Satoru Kusaka; Momoko Usuda; Mariko Kametani; Toshinori Ando; Shinnichi Sakamoto; Chieko Mitsuhata; Mikihito Kajiya; Katsuyuki Kozai; Ryota Nomura (MDPI AG, 2023)
The presence of a supernumerary tooth is one of the most common dental anomalies, and surgical treatment is often required to address this anomaly. Moreover, it may lead to malocclusion, and long-term follow-up is important to monitor its status. A 4-year-and-11-month-old boy was referred to our hospital for dental caries treatment. At 5 years and 5 months of age, a radiographic examination showed a supernumerary tooth (first supernumerary tooth) near the permanent maxillary left central incisor, and it was extracted 6 months later. Eighteen months after the extraction of the first supernumerary tooth, a new supernumerary tooth (second supernumerary tooth) was detected in the same region, which was extracted when the patient was aged seven years and seven months. Seven months later, another supernumerary tooth (third supernumerary tooth) was detected and extracted immediately. However, the permanent maxillary left central incisor did not erupt spontaneously even after 6 months. Therefore, surgical exposure was performed, and the central incisor erupted into the oral cavity. This report describes our experience with this patient with three metachronous supernumerary teeth and their management until the eruption of the permanent tooth. This report highlights the importance of long-term follow-up after supernumerary tooth extraction until the permanent teeth in that region have erupted completely.